2015
DOI: 10.3109/13880209.2014.984855
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal absorption enhancing effect of the essential oil ofRosmarinus officinalison percutaneous absorption of Na diclofenac from topical gel

Abstract: This study proved the enhancing effect of 0.5 and 1% of rosemary essential oil on diclofenac percutaneous absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Moreover, essential oils (EOs) and their volatile constituents have also been identified as one promising group of candidates to be employed as clinically acceptable PEs. Until now, EOs have been shown to be successful in delivering a range of different drugs across the skin, including vitamins (Valgimigli et al 2012), estradiol (Monti et al 2002), labetolol hydrochloride (Jain et al 2008), trazodone hydrochloride (Das et al 2006), tetramethylpyrazine (Shen et al 2013), carvedilol (Amin et al 2008), 5-fluorouracil (5-FU) (Lan et al 2014a), flurbiprofen (Zhang et al 2006;Charoo et al 2008), diclofenac sodium (Akbari et al 2015), indomethacin (Lan et al 2014a) and ibuprofen (Luo et al 2007;Shen et al 2007;Khan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, essential oils (EOs) and their volatile constituents have also been identified as one promising group of candidates to be employed as clinically acceptable PEs. Until now, EOs have been shown to be successful in delivering a range of different drugs across the skin, including vitamins (Valgimigli et al 2012), estradiol (Monti et al 2002), labetolol hydrochloride (Jain et al 2008), trazodone hydrochloride (Das et al 2006), tetramethylpyrazine (Shen et al 2013), carvedilol (Amin et al 2008), 5-fluorouracil (5-FU) (Lan et al 2014a), flurbiprofen (Zhang et al 2006;Charoo et al 2008), diclofenac sodium (Akbari et al 2015), indomethacin (Lan et al 2014a) and ibuprofen (Luo et al 2007;Shen et al 2007;Khan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Terpenes are an effective class of permeation enhancers obtained from natural sources (Akbari et al 2015). Further, quite a few terpenes are included in the list of Generally Recognized As Safe (GRAS) agents issued by the US Food and Drug Administration (US FDA) (Aqil et al 2007;Sapra et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it demonstrated greater sensitivity to these essences. This is probably due to the differences in the strength of the cell wall of gram-negative and gram-positive bacteria and lack of membrane in gram-positive bacteria (24). It is important to know that the compositions in plant extracts may introduce the most effective agent in the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the reaction of bacterial strains to antibiotics, tests showed that all strains reacted similarly to a special antibiotic; this is indicative of low genetic diversity of strains in populations under study. However, the strains responded differently to various types of antibiotics and this is due to the type and mode of action of antibiotics on specific loca- (24). The existence of free radicals in the extract of this plant could also be effective in inhibiting bacteria and the ethyl acetate compound in the extract could create maximum inhibitory effect (25).…”
Section: Discussionmentioning
confidence: 99%